Serious lesions in Green turtles (Chelonia mydas) afflicted by fatal Spirorchiidiasis found stranded in south and southeastern Brazil. (April 2023) - Jerdy, Hassan; Barreto, Bruna; Werneck, Max; Hauser-Davis, Rachel Ann; Baldassin, Paula; Gabriel, Patrick; de Moraes Souza, Aline Luize; Aparecida da Silva, Maria; Felix, Aline; Rodrigues, Rachel Ribeiro; Bianchi, Mariah; Barbosa, Carla; et al.
Abstract: Several diseases have been reported as affecting endangered wild sea turtle population worldwide, including spirorchiidiasis. This parasitic infection results in serious circulatory disorders in sea turtles, as well as tissue damage due to the presence of spirorchiids eggs. However, few reports of organs severely affected by tissue replacement caused by granulomatous inflammatory processes due to spirorchiidiasis in sea turtles are available. In this regard, this study describes massive lesions in 16 juvenile green turtles from southeastern Brazil presenting no other detectable diseases or injuries, associated to parasitic compression of air spaces, parasitic thyroid atrophy, parasitic encephalic compression and parasitic splenic lymphoid depletion. These rare injuries were categorized as extremely severe, affecting most spirorchiidiasis-infected organs. Spirorchiidiasis was, thus, noted herein as capable of causing a variety of lethal injuries to vital or extremely important organs in sea turtles. Spirorchiidiasis should, therefore, also be considered a potential cause of death in stranded green sea turtle monitoring efforts. Graphical abstract: Image 1 Highlights: This study reports a new death cause in Chelonia mydas. Extremely severe atrophic lesions were observed. Lesions were compatible with inefficiency or malfunctioning of several organs. Brain compression and loss of brain mass was associated with large parasitic granulomas. This study demystifies the pathogenic potential of Spirorchiidae family parasites.